Identificación de los síntomas de la Mancha negra (Cercospora purpura), en el cultivo de aguacate (Persea americana) y su método de control - Contreras Cobos, Kevin Steven (2021)
Avocado (Persea americana) can be an option to improve the economy of farmers, transform rural areas and diversify crops, so these projects have become a strategic option for large-scale industries. The global consumption of this fruit is increasing, because it generates employment, economic resources and helps to mitigate and adapt to climate change, as well as having social, economic and environmental benefits. Ecuador produces two varieties of avocados: Fuerte (which represents 99% of national consumption) and Hass (for export). They grow on 800 hectares of land in the provinces of Carchi, Imbabura, Pichincha, Tungurahua, Azuay, Loja and Santa Elena. The black spot (Cercospora purpurea) attacks the leaves and produces small dark brown lesions. When the attack is severe, they will fall and the trees will lose their leaves. In fruit it produces small dark lesions with irregular edges and cracked rind. Damage to the leaves and fruits helps other organisms such as anthracnose to enter. With the preventive measures in cultural control, pruning the crop before the start of the productive stage reduced the incidence of the fungus in fruits by 50%, compared to not carrying out this practice, which allows more light and aeration to the trees, but it is necessary to seal the wounds caused by pruning by applying oil-based paint, with a brush, in the pruned region. It has been experimentally demonstrated that the treatment of avocado fruits, in pre-harvest, with isolates of Bacillus subtilis reduces the severity of the black spot of the avocado in storage. In chemical control based on the rotation of fungicides alone, such as Difenoconazole (0.18 g / L), Tebuconazole (0.20 g / L) + Trifloxystrobin (0.10 g / L); or in a mixture with copper oxychloride, Triadimenol (0.25 g / L) + Azoxystrobin (0.1 g / L)], every 21 days from flowering to harvest.